Pengaruh Dimensi Lingkungan Fisik (Servicescape) Terhadap Niat Beli Hedonis (Studi Pada Chandra Departement Store Mall Boemi Kedaton Bandar Lampung) - M Abirama Permana S; Driya Wiryawan; Dwi Asri Siti A (CV. ITTC INDONESIA, 2025)
The rapid growth of modern retail is driven by changing consumer behavior, which is no longer solely focused on functional needs but also on emotional satisfaction through enjoyable shopping experiences. This study aims to analyze the influence of servicescape dimensions, including ambient conditions, spatial layout and functionality, as well as signs, symbols, and artifacts, on consumers’ hedonic purchase intention at Chandra Department Store, Boemi Kedaton Mall, Bandar Lampung. This research employs a quantitative approach with a survey method. A total of 180 respondents were selected using purposive sampling. Data were analyzed using multiple linear regression with SPSS 26. The results reveal that all three dimensions of servicescape have a positive and significant effect on hedonic purchase intention, both partially and simultaneously. These findings emphasize that the physical store environment plays a crucial role in encouraging consumers to engage in shopping driven by pleasure motives.